Performance evaluation of two models in the reactive routing protocol in manets - Muthanna Jaafar Abbas; Haider Mohammed Turki Alhilfi; Tole Sutikno (Institute of Advanced Engineering and Science, 2021)
Due to the need for the multicast connection required by multimedia applications such as video conferencing and natural disaster management, it was necessary to use a set of portable and connected wireless peripheral devices without the need for infrastructure and without a central router, by use wireless network as